Allah gives us food: the kingdom of Allah - Khan, Saniyasnain; Mazumdar, Siddhartha (Goodword Books New Delhi, 2003)
"Allah Gives Us Food" is a delightful book that teaches children about the blessings of food as a gift from Allah. It emphasizes gratitude, the importance of sharing, and the diverse foods created for our nourishment, fostering a sense of appreciation for nature and sustenance.